Study on the mediation effect of body image between somatization and subjective well-being levels in individuals - Akkaya Kaçmaz, Devrim; Tetik Küçükelçi, Didem; Sahranç, Ümit (Cenk Aksoy, 2023)
The aim of this study is to examine the relationships between subjective well-being, body image, somatization and to reveal the mediating effect of body image. People become more at peace with their bodies as their subjective well-being increases. In addition, subjective well-being and the goodness of body image reduce somatic symptoms. The questionnaire consisting of body image, subjective well being and somatization scales delivered to the volunteer participants. Accordingly, an online survey was conducted with 534 participants between March 2020 and June 2020. SPSS 24.00 package program was used for the analysis of the data obtained from the participants. Cronbach's Alpha coefficients of the scales were calculated in order to perform the reliability analysis of the scales. These values are (0.797), (0.925) and (0.808) for the subjective well-being scale, Body image and somatization scale, respectively, the reliability of the scales was high. Afterwards, descriptive statistics, correlation analysis, regression analysis and mediation effect studies were carried out (p<0.05). According to the results obtained, people with low somatization characteristics have a positive attitude towards life and are physically healthier. In addition, it was concluded that body image has a partial mediating effect on the relationship between somatization and subjective well-being. The decrease in somatic symptoms and the feeling of well-being of people have a negative relationship, and this relationship is supported by being at peace with their bodies and being happy.
Keywords: Body image; Relationship; Somatization; Subjective Well-Being